AICCRA/GMet Farmers Community Engagement - Martey, Francisca; Opoku, Nana Kofi; Lazia, Jeremiah Z. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate Information Services (CIS) is very important for farmers to enable them plan their farming activities during the season. Ghana Meteorological Agency (GMet) and the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) collaborated to train seven Hundred and Eighty-Five (785) in 6 regions of Ghana on CIS and associated advisories.By involving multiple developing the capacity of smallholder farmers, including women, AICCRA and GMet promoted gender inclusion, knowledge sharing, and collaboration. This collaborative approach leads to better insights, collective problem-solving, and improved agricultural outcomes.